Martensitic transformation of FeNi nanofilm induced by interfacial stress generated in FeNi/V nanomultilayered structure - Li, Wei (Springer, 2014)
FeNi/V nanomultilayered films with different V layer thicknesses were synthesized by magnetron sputtering. By adjusting the thickness of the V layer, different interfacial compressive stress were imposed on FeNi layers and the effect of interfacial stress on martensitic transformation of the FeNi film was investigated. Without insertion of V layers, the FeNi film exhibits a face-centered cubic (fcc) structure. With the thickness of V inserted layers up to 1.5 nm, under the coherent growth structure in FeNi/V nanomultilayered films, FeNi layers bear interfacial compressive stress due to the larger lattice parameter relative to V, which induces the martensitic transformation of the FeNi film. As the V layer thickness increases to 2.0 nm, V layers cannot keep the coherent growth structure with FeNi layers, leading to the disappearance of interfacial compressive stress and termination of the martensitic transformation in the FeNi film. The interfacial compressive stress-induced martensitic transformation of the FeNi nanofilm is verified through experiment. The method of imposing and modulating the interfacial stress through the epitaxial growth structure in the nanomultilayered films should be noticed and utilized.